2008
DOI: 10.1111/j.1468-5876.2007.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of the Incidence of Employer Contributions to Social Security in Japan*

Abstract: The present paper estimates the incidence of the employer portion of social security contributions in Japan. One of the purposes of the paper is to examine whether the employer portion is shifted entirely or partly in many industrialized countries. The paper concludes, based on our estimation method, that there is very little apparent backwards shifting on to employees and, therefore, employers bear nearly all of their portion of social security contributions. Firms in Japan could use their contributions to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…For instance, Tachibanaki and Yokoyama (2008) argued that the increase in social security premiums for health insurance, employee's pension insurance and unemployment insurance have not depressed employees' wages using industry-based aggregate data. Hamaaki and Iwamoto (2010) criticized Tachibanaki and Yokoyama (2008) by suggesting their results suffered from a downward bias in that they omitted the upper trend in wages and found at least some shift in the social insurance burden on wages using long-run time-series data. In the short run (as in our study), however, it is very difficult to separate the change in wages caused by cost-shifting from the change in wages caused by broader macroeconomic trends or temporary shocks to the national economy.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Tachibanaki and Yokoyama (2008) argued that the increase in social security premiums for health insurance, employee's pension insurance and unemployment insurance have not depressed employees' wages using industry-based aggregate data. Hamaaki and Iwamoto (2010) criticized Tachibanaki and Yokoyama (2008) by suggesting their results suffered from a downward bias in that they omitted the upper trend in wages and found at least some shift in the social insurance burden on wages using long-run time-series data. In the short run (as in our study), however, it is very difficult to separate the change in wages caused by cost-shifting from the change in wages caused by broader macroeconomic trends or temporary shocks to the national economy.…”
Section: Estimation Resultsmentioning
confidence: 99%
“… The change in HSSE contributions may affect the wage in the long run when they take place continuously. For instance, Tachibanaki and Yokoyama (2008) argued that the increase in social security premiums for health insurance, employee's pension insurance and unemployment insurance have not depressed employees' wages using industry‐based aggregate data. Hamaaki and Iwamoto (2010) criticized Tachibanaki and Yokoyama (2008) by suggesting their results suffered from a downward bias in that they omitted the upper trend in wages and found at least some shift in the social insurance burden on wages using long‐run time‐series data.…”
mentioning
confidence: 99%
“…These values can be estimated with the data. The estimated result of Tachibanaki and Yokoyama (2002) suggests that it is impossible to find any significant shifting except for a few cases of samples divided by sex and industry. It implies that nearly all employers' contributions to social security are borne by employers (i.e., firms).…”
Section: Incidence In Japanmentioning
confidence: 87%
“…Thus investigation of the impact of payroll taxes on workers" wage levels is an important issue. Most previous studies indicate that the payroll tax may decrease the workers" wage (Hamermesh, 1979;Gruber, 1994;Fishback and Kantor, 1995;Anderson and Meyer, 2000;Kugler and Kugler, 2003;Yiwamoto and Hamaaki, 2006;and Sakei and Kazegami, 2007), whereas Gruber and Krueger (1991), Gruber (1994Gruber ( , 1997, and Tachibanaki and Yokoyama (2008) found that the impact of the payroll tax on wage is not statistically significant. Yiwamoto and Hamaaki (2006) even find the wage to be higher when the workers in the enterprise had higher health care payroll taxes.…”
Section: Introductionmentioning
confidence: 96%